(untitled) (Critical Journal of Social Sciences, 2026)
This study examines the influence of religiosity on perceived entrepreneurial motivation (EM) and entrepreneurial self-efficacy (ESE) among business graduates in selected parts of Punjab, focusing on the mediating roles of structural and cognitive social capital. The work follows a positivist philosophy with a deductive approach and a cross-sectional time horizon to test theoretical relationships using empirical data. A sample of 321 business graduates from selected areas of Punjab was selected through convenience sampling due to accessibility and time constraints. Data were collected via a structured questionnaire adapted from previous validated studies. To examine the direct and mediating effects among religiosity, social capital, entrepreneurial motivation, and self-efficacy, Structural Equation Modelling (SEM) was conducted using SmartPLS 4, offering robust analysis of complex relationships within the proposed conceptual framework. The findings revealed a positive influence of religiosity on both entrepreneurial motivation and self-efficacy. Cognitive social capital fully mediates the influence of religiosity on entrepreneurial self-efficacy, while structural social capital positively impacts self-efficacy but does not predict motivation to engage in entrepreneurship. Both religiosity and cognitive social capital have a significant and positive influence on entrepreneurial self-efficacy and motivation, while structural social capital significantly influences self-efficacy. These insights provide a foundation for policymakers and educators to design interventions that incorporate religious and social factors to foster youth entrepreneurship. This study contributes to the existing literature by enhancing the understanding of the factors influencing youth entrepreneurship in a developing country context, particularly by exploring how religiosity and social capital shape entrepreneurial intention and self-efficacy.